Peningkatan Kualitas Sumber Daya Manusia Masyarakat Desa Berbasis Pendidikan Islami dan Potensi Kearifan Lokal di Desa Muktiwari, Kecamatan Cibitung, Kabupaten Bekasi - Nugroho, Arief Teguh; Putra, Maha; Achmad, Yudianto; Wulandari, Anna (Jurnal Pengabdian Masyarakat (Bisma), 2023)
The quality of the process and the results of local excellence are greatly influenced by the available resources, known as the 7M, namely Man (labor), Money (capital), Machine (machines), Material (raw materials), Method (method), Marketing ( marketing), and Management (management). If all of these resources are met, the process and results will be optimal, but on the other hand, if something is missing, the results could be less than satisfactory. Apart from being influenced by resources, this process must also pay attention to market conditions, competitors, potential substitutes, and technological developments. Thus, the final result of this process will be a local product or culture that is of high value, unique, and has advantages compared to similar products from other regions. Meanwhile, the role of the academic team is to prepare a more structured workshop/training concept and empower it by improving the quality of human resources based on Islamic education and the potential of local regional wisdom. Through this collaboration, it is hoped that it will be possible to realize and improve the quality of human resources based on Islamic education and the potential of local regional wisdom owned by Muktiwari Village, Cibitung District, Bekasi Regency.Sumber Daya Manusia Masyarakat Desa; Kearifan Lokal; Pendidikan Islami; Desa Muktiwari